EFFECTIVENESS OF LAWSONIA INERMIS LINNEAUS LEAVES INFUSION IN GINGIVITIS HEALING: EFEKTIFITAS INFUSA DAUN LAWSONIA INERMIS LINNEAUS TERHADAP PENYEMBUHAN GINGIVITIS - Lies Zubardiah; Dewi Nurul Mustaqimah; Elza Ibrahim Auerkari (Dentika: Dental Journal, 2012)
Gingivitis is one type of periodontal disease and it is chronic in nature. The main etiological factor of gingivitis is bacterialplaque. Untreated gingivitis can spread to underlying tissues and it can become periodontitis and produce tissuedestruction. One of the treatments for gingivitis is plaque removal, helped by antibacterial mouthrinsing to reducebacterial plaque. Lawsonia inermis L. leaves have been used by Indonesian villagers for healing skin wounds andreported to show antibacterial effect in vitro and in vivo. This study aimed to determine the effect of Lawsonia inermis L.leaves infusion in gingivitis healing. A total of 63 gingivitis patients devided into 5 groups were instructed to rinse with 3concentrations (50000 µg/mL, 10000 µg/mL, 5000 µg/mL) of Lawsonia inermis L. leaves infusion; 0.1% hexetidinesolution, and placebo as control. Papilla Bleeding Index (PBI) used in measurement for bleeding on probing. The resultshowed that decreasing of PBI in Lawsonia inermis L. leaves infusion at 10000 µg/mL concentratation (80%), wasstronger than hexetidine 0.1% (76%). In conclusion, Lawsonia inermis L. leaves infusion effective to reduce PBI betterthan hexetidine. In conclusion, Lawsonia inermis L. leaves is effective to treat gingivitis.